THE WORLD-CLASS UNIVERSITY AS PART OF A NEW HIGHER EDUCATION PARADIGM: FROM INSTITUTIONAL QUALITIES TO SYSTEMIC EXCELLENCE - SADLAK, Jan; LIU, Nian Cai (2010)
Universitatea de clasa mondiala ca parte a unei noi paradigme de învățămînt superior: de la calitățile instituționale la excelența sistemică.